2016
DOI: 10.1111/eos.12255
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid regulates adhesion molecules and enhances migration of human oral keratinocytes

Abstract: Oral keratinocytes are connected via cell-to-cell adhesions to protect underlying tissues from physical and bacterial damage. Lysophosphatidic acids (LPAs) are a family of phospholipid mediators that have the ability to regulate gene expression, cytoskeletal rearrangement, and cytokine/chemokine secretion, which mediate proliferation, migration, and differentiation. Several forms of LPA are found in saliva and gingival crevicular fluid, but it is unknown how they affect human oral keratinocytes (HOK). The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This suggests an additive or synergistic effect of these compounds. The presented data show that representatives of two compound classes, lignans (4) and diterpene resin acids (5)(6)(7)(8)(9)(10)(11), contribute to increased migration and proliferation of keratinocytes upon exposure to spruce balm. These findings are an initial step in the comprehensive and laborious process from a traditional natural product to a rational phytotherapeutic.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This suggests an additive or synergistic effect of these compounds. The presented data show that representatives of two compound classes, lignans (4) and diterpene resin acids (5)(6)(7)(8)(9)(10)(11), contribute to increased migration and proliferation of keratinocytes upon exposure to spruce balm. These findings are an initial step in the comprehensive and laborious process from a traditional natural product to a rational phytotherapeutic.…”
Section: Resultsmentioning
confidence: 86%
“…These concentrations were chosen as they did not markedly impede HaCaT viability in previous experiments (data not shown). As positive control, we used 10 µM LPA, a substance known to boost migration in different cell-types [11].…”
Section: Resultsmentioning
confidence: 99%
“…Since ccRCC is a metabolic disease that is characterized by changes in the lipidome ( 60 ), it is notable that we have uncovered alterations in the iron metabolic markers following cellular treatment with LPA, a potent lipid mitogen with roles in cancer pathogenesis ( 61 64 ). Specifically, we have demonstrated that LPA alters intracellular labile iron levels and expression of iron metabolic mediators in epithelial cells including FTSECs and RPTECs.…”
Section: Discussionmentioning
confidence: 99%